2010
DOI: 10.1007/s00284-010-9674-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Optimization of Indole-3-Acetic Acid Production and Phosphate Solubilization from Rhizobacteria Aimed at Improving Plant Growth

Abstract: A total of 216 bacterial strains were isolated from rice rhizospheric soils in Northern Thailand. The bacterial strains were initially tested for solubilization of inorganic phosphate, indole acetic acid (IAA) production, selected strains were then tested for optimized conditions for IAA production and whether these caused stimulatory effects on bean and maize seedling growth. It was found that all strains had solubilized inorganic phosphate (P), but only 18.05% produced IAA. The best IAA producer was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 22 publications
4
56
3
2
Order By: Relevance
“…The limits of detection for all studied analytes were below 0.015 μg mL −1 (Table 1). These results, together with the fact that the concentrations of indolic compounds accumulating in bacterial cultures typically reaches from a few to several dozens of μg mL −1 (Ahmad et al 2005; Khakipour et al 2008; Chaiharn and Lumyong 2011), indicate that no additional enrichment of the biological sample is required. Therefore, instead of time- and reagent-consuming organic solvent extraction, we utilized a single centrifugal filtration step for sample preparation.…”
Section: Resultsmentioning
confidence: 97%
“…The limits of detection for all studied analytes were below 0.015 μg mL −1 (Table 1). These results, together with the fact that the concentrations of indolic compounds accumulating in bacterial cultures typically reaches from a few to several dozens of μg mL −1 (Ahmad et al 2005; Khakipour et al 2008; Chaiharn and Lumyong 2011), indicate that no additional enrichment of the biological sample is required. Therefore, instead of time- and reagent-consuming organic solvent extraction, we utilized a single centrifugal filtration step for sample preparation.…”
Section: Resultsmentioning
confidence: 97%
“…and Bacillus sp. However, Chaiharn and Lumyong (2011) reported extremely high IAA production (291.97 g/ml) and phosphate solubilization (334 g/ml) with strain Klebsiella SN 1.1 isolated from rice rhizospheric soils in Northern Thailand. It has been reported that microbial IAA promotes root growth either directly by stimulating plant cell elongation or cell division or indirectly by its influence on the ACC deaminase activity (Patten and Glick, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Besides, the production of chelating substances H 2 S, CO 2 , mineral acids, siderophores, biologically active substances like indole acetic acid [119], gibberellins and cytokinins Penicillium bilaii Citric and oxalic acid [105] Penicillium regulosum Citric and gluconic acid [106] Pseudomonas aeruginosa Gluconic [97] Pseudomonas putida Gluconic acid [107] Pseudomonas sp. Citric, gluconic [108] Pseudomonas sp.…”
Section: Other Theories Of Mineral Phosphate Solubilizationmentioning
confidence: 99%